1999
DOI: 10.1076/orbi.18.2.83.2720
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes following dacryocystorhinostomy: external and endonasal laser techniques compared

Abstract: AIMS/BACKGROUND. Endonasal laser dacryocystorhinostomy (ELDCR) has recently become established as an alternative technique to conventional external DCR (EXDCR) for relief of epiphora. The aim of this study was to compare quality of life and symptomatic outcomes in patients treated by these two methods. METHODS. A postal questionnaire was sent to 204 ELDCR and 78 EXDCR patients who had undergone surgery under our care more than 6 months previously. The questionnaire included the validated 18-item Glasgow Benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 8 publications
5
56
0
10
Order By: Relevance
“…We can also support the findings of Bakri et al[ 10] who found a significant improvement in the patient’s subjective opinion of quality of life after dacryocystorhinostomy. The patient’s subjective evaluation of the EDCR results is probably the most important item to evaluate the outcome of the operation.…”
Section: Discussionsupporting
confidence: 81%
“…We can also support the findings of Bakri et al[ 10] who found a significant improvement in the patient’s subjective opinion of quality of life after dacryocystorhinostomy. The patient’s subjective evaluation of the EDCR results is probably the most important item to evaluate the outcome of the operation.…”
Section: Discussionsupporting
confidence: 81%
“…15 13.3 Laser DCR 16 16.8 Acoustic neuroma surgery 17 26.6 Ã Present study. GBI ¼ Glasgow benefit inventory; CI ¼ confidence intervals; FESS ¼ functional endoscopic sinus surgery; BAHA ¼ bone-anchored hearing aid insertion; DCR ¼ dacryocystorhinostomy N J CALDER, I R C SWAN 1062…”
Section: Resultsmentioning
confidence: 97%
“…15,16 The success rate for endonasal DCR (endo-DCR) has been reported as comparable to external DCR by some authors, [17][18][19][20] but less successful than external DCR by others. [21][22][23][24] The primary procedure success rate in our series was 95.2%. Five of 104 cases needed revision DCR for resolution of symptoms, and 84% of our patients were asymptomatic or had occasionally mild epiphora after the initial procedure.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, it can simultaneously treat any associated nasal pathology, 3,24,27 and can be performed simultaneously on both sides under general anaesthesia as a day procedure. A recent report indicated that despite a narrower nasal cavity in children, removal of bone was relatively easy and no difficulty or difference in the procedure was found in comparison with adults.…”
Section: Discussionmentioning
confidence: 99%